Spatial patterns of the frog Oophaga pumilio in a plantation system are consistent with conspecific attraction. Issue 5 (14th February 2018) - Folt, Brian; Donnelly, Maureen A.; Guyer, Craig
Abstract: The conspecific attraction hypothesis predicts that individuals are attracted to conspecifics because conspecifics may be cues to quality habitat and/or colonists may benefit from living in aggregations. Poison frogs (Dendrobatidae) are aposematic, territorial, and visually oriented—three characteristics which make dendrobatids an appropriate model to test for conspecific attraction. In this study, we tested this hypothesis using an extensive mark‐recapture dataset of the strawberry poison frog ( Oophaga pumilio ) from La Selva Biological Station, Costa Rica. Data were collected from replicate populations in a relatively homogenous Theobroma cacao plantation, which provided a unique opportunity to test how conspecifics influence the spatial ecology of migrants in a controlled habitat with homogenous structure. We predicted that (1) individuals entering a population would aggregate with resident adults, (2) migrants would share sites with residents at a greater frequency than expected by chance, and (3) migrant home ranges would have shorter nearest‐neighbor distances (NND) to residents than expected by chance. The results were consistent with these three predictions: Relative to random simulations, we observed significant aggregation, home‐range overlap, and NND distribution functions in four, five, and six, respectively, of the six migrant–resident groups analyzed. Conspecific attraction may benefit migrant O. pumilio by providing cues to suitable home sites and/or increasing the potential for social interactions with conspecifics; if true, these benefits should outweigh the negative effects of other factors associated with aggregation. The observed aggregation between migrant and resident O. pumilio is consistent with conspecific attraction in dendrobatid frogs, and our study provides rare support from a field setting that conspecific attraction may be a relevant mechanism for models of anuran spatial ecology. Abstract : We used a two‐year mark‐recapture study of the strawberry poison frog ( Oophaga pumilio ) in a homogenous cacao plantation in Costa Rica to evaluate whether patterns of spatial ecology are consistent with conspecific attraction. Measures of migrant space use at two temporal scales suggested that migrants were significantly aggregated and exhibited significant home‐range overlap with residents. These results are consistent with necessary predictions of conspecific attraction.